The Biosocial Body: HIV Visibility in an Age of Pharmaceutical Treatment in Indonesia. (21st February 2022) - Hegarty, Benjamin
Abstract: Peer outreach workers play a pivotal role in assisting HIV‐positive people to access pharmaceutical treatment. In their role mediating between everyday sexual cultures and biomedical knowledge, outreach workers for men who have sex with men in Indonesia's capital city Jakarta emphasize the need to manage the visibility of the HIV‐positive body as it appears to others. In order to enter clinical spaces, clients must adopt neat attire, strive to embody a physique that is robust, and maintain a clear skin tone. Clients must also learn to gain mastery over their gender performance as a revelation of their sexuality. Outreach workers interpret the individual sexual and HIV‐positive status of their clients as either "open" or "closed" in relation to their audience, an understanding that generates a demand for self‐discipline directed at outer appearances. Attending to paradigms of visibility that discipline the biosocial body reveals the social relations necessary for accessing treatment.